The interplay between DNA damage response and mitochondrial dysfunction in radiotherapy - Yang, Shuhua; Li, Yuke; Zhang, Jinlang; Shen, Aihua; Hu, Burong; Yan, Junfang (Frontiers in Oncology, 2025)
Radiotherapy plays a crucial role in cancer management by directly eliminating cancer cells, reducing the likelihood of recurrence and metastasis, and preserving the functionality of essential organs. Nonetheless, the radioresistance of cancer cells in radiotherapy poses a significant challenge. The DNA damage response (DDR) serves as a protective mechanism against DNA damage, associating with various intrinsic factors and significantly contributing to radioresistance. Furthermore, the function and status of mitochondria are closely linked to the resistance of cancer cells to radiotherapy. The effects of radiation on nuclear and mitochondrial structures are not independent; they interact through bidirectional signaling pathways to affect cellular radioresistance. This review summarizes and discusses the regulatory mechanisms of DDR and mitochondrial function in radiotherapy from the perspectives of anterograde and retrograde signaling, aiming to provide valuable insights into how cells respond to radiation to determine their fate, and to offer new strategies for precise radiosensitization through the coordinated regulation of nuclear-mitochondrial signaling networks in the future.